Entrepreneurs and Empire. The Murašû Archive, the Murašû Firm, and Persian Rule in Babylonia - Stolper, Matthew W. (1985)
Appendix II: 120 selected texts from the Murašû archives in the University Museum and the British Museum. Autographie und Umschrift; vgl. Index der Museumsnummern p. 305-306.